ANALISIS ENERGI PADA BERBAGAI MATERIAL DINDING (BATA, BATAKO DAN BATA RINGAN) - Sri Novianthi Pratiwi (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2020)
In building design, the selection of building materials is one aspect that needs to be considered. Building materials are components that require energy in the manufacturing process. In the process of building material production, the use of energy at each stage becomes one of the parameters of CO2 carbon emission levels. The higher the use of fossil energy, the higher the CO2 emissions and the risk of causing global warming. Bricks, concrete blocks, and lightweight bricks are the types of materials commonly used to make building walls. The selection of wall materials is still largely related to price or aesthetic considerations, but the assessment of the level of environmental friendliness is still lacking in attention. This study tries to analyse the life cycle of energy in wall materials (bricks, concrete blocks and lightweight bricks). From the research results obtained, concrete block is the lowest material in the use of production energy.